Did Islamic Leadership Influence Online Learning Systems? - Masduki Asbari; Dewiana Novitasari (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine and analyze the effect of Islamic leadership of leaders at the Islamic Schools in Tangerang on the information system success model (system quality, information quality, service quality). The number of research samples was 98 teachers. The sampling technique used is simple random sampling. The analytical method used is SEM with the help of SmartPLS 3.0 software. The results showed that the role of Islamic leadership had a significant effect on the three variables of the information system success model. This research can be used as a basis for the next similar research in the schools, which until now is still relatively minimal exploration.